The dynamics of physical development of 6-years-old children in Lviv - Fedorenko, V.I.; Kitsula, L.M. (Environment & Health, 2017)
Objective. We studied the regularities of the dynamics of physical development of the children aged 6 years in Lviv city for the period from 1969 to 2015 by the anthropometric parameters and assessed physical development of the children at modern stage.Materials and methods. The results of the anthropometric measurements in 1969-1971, 1992-1993, 1995-1996, 2003-2005, 2014–2015 were the basis for the analysis of the dynamics of physical development of the children. For the assessment of physical development of the children, examined in 2014-2015, we calculated the body mass index, Pignet’s index, proportionality of thorax. The anthropometric indices of the children were compared with the hygienic standards of 2013. Statistical analysis was carried out by the least squares method with a determination of the authenticity of the results by Student’s t-test.Results. The dynamics of physical development of the children aged 6 years in Lviv during the period from 1969 to 2015 was found to be characterized by the processes of decelerations and acceleration of the growth rates of the anthropometric indices. The lowest values of stature and body weight of the children were observed from 1992 to 1996 that was probably due to the irrational nutrition and the intake of the pollutants from environment and food products, heavy metals in particular. The highest anthropometric indices were observed in 2014- 2015. The values of body mass index indicate the harmonious development of 59.0% of girls and 55.3% of boys. Dolichomorphic body type in 96.9% of girls and 85.9% of boys is characterized by Pignet’s index, the narrow thorax in 79.7% of girls and 76.3% of boys with increased growth testifies about the processes of gracialization. In comparison with the Criteria for the Evaluation of Physical Development of the Children in Ukraine (2013) 6-years-old boys and girls in Lviv are higher and have a bigger chest circumference, and boys have a bigger body weight than their peers, that indicates the expediency of the development of regional criteria for physical development.
Keywords: physical development; dynamics; body weight; stature; 6-years-old children; anthropometric indices